Geophysical Evidence for Magmatism Southwest of the Brothers Islands, Northern Red Sea (Offshore Quseir, Egypt). Issue 10 (14th October 2022) - Ali, Moamen; Ligi, Marco; Ceriani, Andrea; Bouchaala, Fateh; Bosworth, William; Decarlis, Alessandro
Abstract: The Red Sea formed as a consequence of Cenozoic rifting between the African and Arabian plates. While continuous oceanic spreading is active in the southern and central sectors, in the northern Red Sea, exposure of oceanic crust is limited to a few along‐axis isolated deeps. However, several off‐axis magmatic edifices have been recognized in this sector, their description in terms of relative age and architectural features remains vague. One of these, offshore Quseir corresponding to a kilometer‐size structural high, was studied in detail using 3D industrial seismic data. This structure is interpreted as due to the coalescence of different volcanic edifices developed on the footwall of a major rift‐related normal fault. Magnetic and gravity data and forward modeling suggest a volcanic nature of the substratum underlying the morphological relief. A similar volcanic origin is proposed for other neighboring basement hills that show a similar magnetic signal. Relationships with the imaged seismo‐stratigraphic sequences point to a Pleistocene age for the magmatic event. Arabian alkali‐basalts, at the same latitude as Quseir, show ages comparable to those inferred for the volcano edifice studied, suggesting a similar geotectonic context. In western Arabian plate, large alkali‐lava fields ( Harrats ) developed along rift‐related faults since the early stages of the Red Sea rift (Late Oligocene). They display a significant northward rejuvenation trend that may be explained by the progressive propagation of the Afar mantle plume. Key Points: The northern Red Sea has been interpreted as the result of a magma‐poor rifting event, but several recent magmatic additions are recognized The basement ridge southwest of the Brothers Islands is interpreted as a volcanic elliptical edifice The relationships with the local inferred stratigraphy suggest a probable Pleistocene age for the magmatic event